Al-Amru and an-Nahyi in Surah Al- Imran (The Research of Balaghah Elements) - Nazwa, Radiatun (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2023)
This study used descriptive qualitative method. The sources of data in this study consisted of primary and secondary data, primary data, namely from the AlQur'an, namely surah al-Imran, and secondary data from books related to the theme of this research. This research is a library research, namely collecting data and information through materials contained in the library. The results of the study show that there are 40 verses of Amar and 10 verses of Nahi in surah al-Imran. And the meaning of the verses that contain Amar include 7 verses with the original meaning (hakiki) and 9 sentences with the meaning of irshad, 11 sentences of Tahdid, 9 sentences of doa , 1 sentence of Ta'jiz, 2 sentences of Takwin, 1 sentence of Takhyir, iltimas 1 sentence, addawam 1 sentence, ta'ajub 1 sentence. And the meaning of verses that contain Nahi, among others, is one verse of original meaning, and with the meaning of Irshad 5 sentences, Do'a 1 sentence, and I'tinas 1 sentence.Keywords: Al-amru, An-nahyi, Surah Al- Imran